2012
DOI: 10.1016/j.ceca.2011.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a disulfide bridge essential for structure and function of the voltage-gated Ca2+ channel α2δ-1 auxiliary subunit

Abstract: Voltage-gated calcium (CaV) channels are transmembrane proteins that form Ca2+-selective pores gated by depolarization and are essential regulators of the intracellular Ca2+ concentration. By providing a pathway for rapid Ca2+ influx, CaV channels couple membrane depolarization to a wide array of cellular responses including neurotransmission, muscle contraction and gene expression. CaV channels fall into two major classes, low voltage-activated (LVA) and high voltage-activated (HVA). The ion-conducting pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 53 publications
2
33
0
Order By: Relevance
“…[78][79][80] Four separate genes code for the a 2 d subunits which display distinct tissue distribution and strong expression in the developing and mature CNS. [74][75][76] The a 2 d proteins consist of post-translationally cleaved a 2 and d peptides which remain associated with each other by a single disulphide bond, 81 and glycosylation of a 2 d seems to be required for the functional membrane expression of Ca V channels. [82][83][84] Molecular topology studies show that the a 2 d subunits may be linked to the plasma membrane via a GPI-anchor or by the d subunit that might constitute a single-pass membrane protein.…”
Section: Ca V 3 (T-type) Channel Transcriptional Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…[78][79][80] Four separate genes code for the a 2 d subunits which display distinct tissue distribution and strong expression in the developing and mature CNS. [74][75][76] The a 2 d proteins consist of post-translationally cleaved a 2 and d peptides which remain associated with each other by a single disulphide bond, 81 and glycosylation of a 2 d seems to be required for the functional membrane expression of Ca V channels. [82][83][84] Molecular topology studies show that the a 2 d subunits may be linked to the plasma membrane via a GPI-anchor or by the d subunit that might constitute a single-pass membrane protein.…”
Section: Ca V 3 (T-type) Channel Transcriptional Regulationmentioning
confidence: 99%
“…[82][83][84] Molecular topology studies show that the a 2 d subunits may be linked to the plasma membrane via a GPI-anchor or by the d subunit that might constitute a single-pass membrane protein. 81,[85][86][87] The majority of the a 2 d subunit is extracellular ( Fig. 1) and ideally located to interact with constituents of the extracellular matrix or extracellularly exposed proteins and serve also as a membrane receptor for binding of anti-epileptic and anti-allodynic drugs.…”
Section: Ca V 3 (T-type) Channel Transcriptional Regulationmentioning
confidence: 99%
“…As mentioned earlier, during biosynthesis the Ca V α 2 δ subunits are generated as precursor proteins which undergo post‐translational cleavage, oxidation, and glycosylation to yield mature proteins comprised of disulphide‐linked α 2 and δ glycopolypeptides . Although the precise functional role of the post‐translational modifications of the Ca V α 2 δ subunits has not yet been fully defined, it has been suggested that they could play a role in channel trafficking.…”
Section: The Cavα2δ Subunitsmentioning
confidence: 99%
“…Disulfide bond formation seems to be also important for channel cell surface expression. Recent studies have shown that a pair of conserved cysteine residues at positions 404 and 1047, located in the vWFA region of α 2 and the extracellular domain of δ, respectively, form a single intermolecular disulfide bridge required for normal α 2 δ‐1 subunit function . In these studies, it was shown that whereas there was a significant increase in current density through Ca V 2.2α 1 /β 3 channels upon cotransfection with wild‐type Ca V α 2 δ‐1, Cys404Ser, and Cys1047Ser mutations had little influence in current density, implying that formation of an intra‐subunit disulfide bond between these residues is essential for Ca V α 2 δ‐1 functional enhancement of currents, and perhaps for Ca V channel trafficking to the plasma membrane.…”
Section: The Cavα2δ Subunitsmentioning
confidence: 99%
See 1 more Smart Citation